Torrefaction of biomass: A review of production methods for biocoal from cultured and waste lignocellulosic feedstocks. (November 2019) - Barskov, Stan; Zappi, Mark; Buchireddy, Prashanth; Dufreche, Stephen; Guillory, John; Gang, Daniel; Hernandez, Rafael; Bajpai, Rakesh; Baudier, Jeff; Cooper, Robbyn; Sharp, Richard
Abstract: Torrefaction is a developing thermal process that has mainly been used to convert lignocellulosic feedstocks, both cultured and wasted, into a "charred" product that can be used as a fuel for power plants, combustion units, and gasifiers. Beneficial characteristics of torrefied products are increased energy density, removal of free water from the feedstock so that water is not being transported to the use facility, grindability indices similar to coal, and a more bio-stable product better suited for outdoor piled storage over the raw input material. A thorough review of the literature involving the torrefaction of fibrous agricultural wastes, food wastes, and non-lignocellulosic wastes (bacteria, algae, yeast, etc.) is presented in this paper. In general, average torrefaction operating conditions yielded greatly improved biofuels over the raw input feedstocks. Highlights: Torrefaction is a feedstock flexible process can produce high-quality biocoal. Process flexibility has been controlled mainly by temperature and reaction time. Numerous studies support using torrefaction for producing a good bio-based fuel. More scale-up work is needed to increase commercialization of the technology.